PENGARUH FINANCIAL TECHNOLOGY DAN PENGGUNAAN ASET TERHADAP KINERJA KEUANGAN DENGAN EFISIENSI OPERASIONAL SEBAGAI VARIABEL MEDIASI PADA BANK DIGITAL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nurlaela, Nurlaela; Samsu G; Musfira, Ria; Abadi, Indra; Adriani, Adriani (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze the influence of fintech and asset utilization on financial performance, with operational efficiency as a mediating variable, in digital banks listed on the Indonesia Stock Exchange (IDX). Using quantitative data from digital banks' financial reports for the 2021–2024 period, this study examines how the development of financial technology (fintech) and asset utilization affect banks' profitability and financial stability through increased operational efficiency. Sampling in this study was conducted considering relevant and specific criteria to ensure the results reflect the actual conditions of the population studied. The sample was selected from digital banks listed on the Indonesia Stock Exchange in 2024, with complete financial and operational data for at least the past two years. Inclusion criteria included 15 digital banks officially operating and having complete financial reports from 2021 to 2024, representing 75 sample units. The sampling technique used was purposive sampling. The data analysis tool used was SEM (Structural Equation Modeling). The analysis shows that fintech significantly accelerates service innovation and expands market access, thus contributing significantly positively to operational efficiency and financial performance. Optimal asset utilization also plays a crucial role in reducing credit risk and improving portfolio quality, ultimately improving operational efficiency and financial performance. Operational efficiency has been shown to contribute significantly positively to financial performance. Operational efficiency has been shown to be a mediating variable that strengthens the relationship between fintech, asset utilization, and financial performance. This study provides important implications for policymakers and digital bank management in optimizing operational strategies and technology investments to enhance competitiveness in the increasingly dynamic digital financial market.